Estudo de proteases extracelulares de Aeromonas spp - Zacaria, Jucimar (My University, 2014)
Aeromonas are ubiquitous water-borne Gram-negative bacteria. Some species of this genus are opportunistic pathogens of a variety of aquatic and terrestrial animals, including humans. Several virulence determinants, such as enterotoxins, hemolysins and hydrolytic enzymes, have been implicated in their ability to cause diseases. Extracellular proteases may be regarded as important enzymes in the mechanisms that confer the metabolic versatility that allow Aeromonas to persist in aquatic habitats, to interact with other organisms, and to cause diseases. In this context, the objective of this work was to assess the extent of differences in extracellular proteases activity and electrophoretic profiles among Aeromonas strains, the substrate specificity among Aeromonas proteases, and the cloning and heterologous expression of Aeromonas elastase. The results showed that A. hydrophila has the highest proteolytic activity with no significant difference between clinical and environmental isolates. Protease zymograms of Aeromonas isolates showed different profiles with 0 to 5 bands, corresponding to metallo, serine and other proteases. Two proteases (56 KDa and 22 KDa) showed activity against a large spectrum of substrates. Caseinolytic activity of A. hydrophila IBAer 109 showed a typical "quorum sensing" behavior, and was induced by gelatin and repressed by glucose, citrate and ammonium. The elastase gene (ahyB) of A. hydrophila ATCC7966 was cloned and expressed in E. coli under the control of lac promoter. The transformant showed both periplasmic and extracellular proteolytic bands of 63 and 38KDa, indicating partial maturation and secretion difficulties.
Aeromonas são bactérias Gram-negativas aquáticas. Algumas espécies deste gênero são patógenos oportunistas de muitos animais aquáticos e terrestres, inclusive o homem. Vários fatores de virulência, tais como enterotoxinas, hemolisinas e outras enzimas, tem sido associados com a sua patogenicidade. As proteases extracelulares devem ser vistas como importantes enzimas envolvidas na versatilidade metabólica que possibilitam as Aeromonas persistir nos ambientes aquáticos, interagir com outros organismos, e causar doenças. Neste contexto, o objetivo deste trabalho foi avaliar: as diferenças nas atividades de proteases extracelulares e o perfil eletroforético entre espécies e isolados de Aeromonas, a especificidade por substratos de poteases de Aeromonas, e a clonagem e expressão heteróloga da elastase de Aeromonas. Os resultados mostraram que A. hydrophila apresenta maior atividade proteolítica, sem, entretanto exibir diferenças significativas entre isolados clínicos e ambientais. Zimogramas proteolíticos dos isolados de Aeromonas demonstraram diferentes perfis com 0 a 5 bandas, correspondendo a metalo, serino ou outras proteases. Duas proteases (56K Da e 22 KDa) apresentaram atividade sobre um grande espectro de substratos. A atividade caseinolítica de A. hydrophila IBAer 109 mostra um típico comportamento de "quorum sensing", sendo induzida por gelatina e reprimida por glicose, citrato e amônio. O gene da elastatse (ahyB) de A. hydrophila ATCC7966 foi clonado e expresso em E. coli sob controle do promotor lac. O transformante apresentou bandas proteolíticas de 63 e 38 KDa no espaço periplasmático e extracelular, indicando maturação parcial e dificuldade de secreção desta enzima.
Keywords: MICROBIOLOGIA; Aeromonas; Proteases extracelulares; Zimogramas; Especificiadde das proteases; Elastase; Bactérias; Microbiologia; Biotecnologia